Pengaruh Power Lengan Terhadap Kemampuan Smash Ditinjau Dari Panjang Lengan Pada Pemain Bulutangkis DI Kabupaten Takalar - Warfahmi Arif; Sarifin G; Andi Atssam Mappanyukki (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2021)
This experimental research aims to determine the effect of arm power on the smash ability of badminton in terms of arm length consisting of long and short. This research was conducted at the Badminton Juang Lapris Building, Takalar Regency from December to January 2021.The experimental method used "two groups pre-test post-test design" ,. The sample consisted of 20 badminton players in Takalar Regency which were divided into two groups. Each group consists of 10 badminton players in Takalar Regency. The data analysis technique is the analysis with Tukey's test at a significance level of α = .05.The results of this study indicate that (1). There is an effect of arm power on the smash ability of badminton players in Takalar Regency in terms of long arm length. This is evidenced by the results of statistical analysis using the Tukey test, where Qhit = 5.79> Qtab (0.05) = 4.33 (2). There is no effect of arm power on the smash ability of badminton players in Takalar Regency in terms of short arm length. This is evidenced by using the Tukey test, where Qhit = 1.16> Qtab (0.05) = 4.33 (3). There is a difference in the effect of arm power on the smash ability of a badminton player in Takalar Regency between the length of the long arm and the length of the short arm. This is evidenced by the results of statistical analysis using the Tukey test, where Qhit = 6.74> Qtab (0.05) = 4.33